A study on the integration of marketing mix to improve performance (with special reference to Cargosave (M) Sdn. Bhd.) / Ahmad Fauzi Abu Kassim - Abu Kassim, Ahmad Fauzi (1993)
Cargosave (M) Sdn.Bhd. is one of the freight forwarding company which have corporatised two years ago. As a new company entered in this competitive industry, Cargosave face a problems in terms of their marketing. Thus, the objective of this thesis is to study the current marketing situation, made an analysis on the research carried out and come up with possible solution to overcome the problem by only concentrating on its 4 elements of marketing mix. (Service, price, place and promotion).